PENGARUH IKLAN MEDIA SOSIAL DAN PEMBERIAN DISKON TERHADAP MINAT BELI KONSUMEN (STUDI PADA KONSUMEN GRABFOOD DI KOTA LAMONGAN) - Nina Elvira Febianti; Anggraeni Sovi Maria Septiana; Maulidza Nur Fauzi; Imtinan Widhah Kumala; Bayu Malikhul Askhar (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to determine the influence of social media advertising and discounts on Grabfood consumers' buying interest in Lamongan City. This research method uses quantitative methods. The population in this research is Grabfood consumers in Lamongan City. The sample used in this research was the entire population, namely 100 respondents, with a sampling technique using accidental sampling. The data analysis technique used in this research is multiple linear regression analysis. The hypothesis testing technique in this research was carried out using SPSS 25 software. The results of data analysis show that social media advertising positively and significantly influences consumer buying interest, then discounts positively and significantly influence consumer buying interest. Together, social media advertising and discounts have a positive and significant effect on Grabfood consumer buying interest in Lamongan City.